Navigating Healthcare Challenges Text Analytics, Data Integration, and Decision-Making in the COVID-19 Era - Shujana (Jejaring Penelitian dan Pengabdian Masyarakat, 2024)
In the context of the COVID-19 pandemic, Integrated Healthcare Systems have emerged as crucial components in effectively managing healthcare challenges. This study delves into the multifaceted role of integrated systems, with a particular focus on the pivotal aspects of text analytics. An exploration of various applications of text analytics unfolds, shedding light on its diverse utility within the healthcare landscape. Extensive reviews of problems encountered by different organizations and insights gleaned from research contribute to a comprehensive understanding of the challenges faced by Health and Human Services (HHS). These challenges, intricately linked to issues such as hospital strains and consumers' personal experiences, are thoroughly examined to provide actionable solutions. A key emphasis is placed on the indispensability of data integration, and the abstract discusses how various analytic approaches can be strategically employed within a well-integrated database system. The nuances of implementing an integrated model are scrutinized, highlighting the primary challenges that organizations, particularly HHS, may encounter. Subsequently, potential solutions are presented, leveraging the power of OLAP to construct a dashboard tailored to address the identified problems. Beyond the technical intricacies, the abstract explores the ramifications of an integrated approach on decision-making processes within HHS. The discussion extends to the acceleration of decision-making possibilities, underlining the imperative need for timely and informed actions in the face of healthcare challenges. In essence, this study provides a nuanced exploration of the role of Integrated Healthcare Systems during the COVID-19 pandemic, incorporating insights from text analytics, data integration, and analytic methodologies. The findings aim to contribute valuable perspectives to healthcare organizations, particularly HHS, as they navigate and mitigate the complexities posed by the ongoing global health crisis.